A new species of wolf-spider (Alopecosa ogorodica sp.n.) from the Russian Mountain Altai with remarks on Arctosa meitanensis Yin et al., 1993 (Araneae: Lycosidae) - Trilikauskas, Laimonas A.; Azarkina, Galina N. (Zootaxa, 2014)
Alopecosa ogorodica sp.n. (♂♀), a new wolf-spider species (Lycosidae) from the Russian Mountain Altai is described. New data, diagnosis, description and drawings on Arctosa meitanensis Yin et al., 1993 are provided.